2023
DOI: 10.3390/su151310490
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning to Smart Cities in Gulf Cooperation Council Countries: The Role of Leadership and Organisational Culture

Abstract: The concept of Society 5.0, first introduced by Japan in 2016, has become a widely accepted model for the development of social infrastructures across the world. It is a model which is expected to take root globally over the next few years. It is also a model which has smart cities, which are connected and inclusive, at its core. The role of open data is critical to smart cities, and the ability to design and implement strategies for its use is a crucial element in their growth and success. This requires a lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…This positive association seems to also occur in the context of smart cities, as studies such as Li et al [46] and Huang et al [30] found that the sense of gain felt by individuals, in residing in a smart city, strongly affected their sense of citizenship attitude and their readiness to participate in the development of the initiative. Another study, in Hong Kong, found that enthusiasm for the smart city concept associated positively with perceived smart city benefits, though the strength of the association was a function of education level and income [47], while research by Georgiadis et al [48], concluded that inadequate dissemination by the government of information about smart city benefits had led to low levels of support and cooperation from the Cypriot public. This paper therefore proposes the hypothesis: Hypothesis 2 (H2).…”
Section: Hypothesis 1 (H1) Information Availability Is Positively Ass...mentioning
confidence: 98%
“…This positive association seems to also occur in the context of smart cities, as studies such as Li et al [46] and Huang et al [30] found that the sense of gain felt by individuals, in residing in a smart city, strongly affected their sense of citizenship attitude and their readiness to participate in the development of the initiative. Another study, in Hong Kong, found that enthusiasm for the smart city concept associated positively with perceived smart city benefits, though the strength of the association was a function of education level and income [47], while research by Georgiadis et al [48], concluded that inadequate dissemination by the government of information about smart city benefits had led to low levels of support and cooperation from the Cypriot public. This paper therefore proposes the hypothesis: Hypothesis 2 (H2).…”
Section: Hypothesis 1 (H1) Information Availability Is Positively Ass...mentioning
confidence: 98%
“…Tourists can easily obtain information about local attractions, public transport, cultural events and even health services, which contributes to a convenient and hassle-free exploration of the city. For smart city residents, roaming at no additional cost becomes an important tool for quick communication and access to important information in their daily lives [49].…”
Section: Roaming Without Additional Charges and Smart City: Transform...mentioning
confidence: 99%
“…Strong commitment will encourage positive IS behavior; otherwise, negative security behavior can become predominant (Dong et al, 2021). Thus, it is important to align employee interests with organizational interests (Carmi & Bouhnik, 2020;Khando et al, 2021;Mutambik et al, 2023a). In this regard, committed employees are more likely to invest in career development and promotions, less likely to violate ISPP, and more likely to see compliance as imperative (Hwang & Um, 2021).…”
Section: Commitmentmentioning
confidence: 99%